The Medicalisation of Childbirth - Paska, Danijela (Svetovi (Ljubljana), 2026)
Beyond its biological functions, reproductive health represents a powerful discursive field. Women’s reproductive health has been and continues to be regulated by societal norms, reli-gious doctrines, and political policies. This article examines how regulatory forces manifest in the medical management of childbirth in Croatian public hospitals, particularly through the medicalisation of birth and the adoption of a technocratic model of care. In this tech-nocratic paradigm, the female body is perceived as a reproductive machine, the woman is objectified, and medical personnel become alienated.
Keywords: Antropologija; biomoč; biopower; Etnologija; gender; Javne bolnišnice; medical care; medicalization; Medicinska antropologija; medikalizacija; Porod; public hospitals; reproductive health; reproduktivno zdravje; spol; Tehnokracija; zdravstvena oskrba; Zdravstveno varstvo